Peran Karakter Wirausaha, Orientasi dan Keunggulan Bersaing Terhadap Keberhasilan Usaha Pada Usaha Cafe di Kabupaten Jember - Andrani, Vevina Talitha; Santoso, Budi; Rahayu, Jekti (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The rapid growth of the café business sector in Jember Regency reflects the intense competition in the local culinary industry, which demands entrepreneurs to possess competitive advantages and adaptive capabilities. The success of café businesses is not only determined by external factors but is also strongly influenced by internal factors of the entrepreneurs, such as entrepreneurial character, entrepreneurial orientation, and the ability to create competitive advantages. This study aims to analyze the influence of entrepreneurial characteristics, entrepreneurial orientation, and competitive advantage on the business success of cafés in Jember Regency, both partially and simultaneously. The method used is a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 86 café entrepreneurs and analyzed using multiple linear regression with the help of SPSS. The results show that all three independent variables have a positive and significant effect on business success, both partially and simultaneously, with entrepreneurial orientation being the dominant factor. These findings highlight the importance of synergy between personal character strength, an innovative mindset, and differentiation ability in building a competitive and sustainable café business.